Implicações de um acervo de arte, virtual e universitário - Ana Beatriz Barroso (EccoS – Revista Científica)
In this paper is proposed an approach to the creative process of an art archive in the cyberspace. It is developed the perception of a language changed by the action of everyone who speaks inventively. Afterwards it discusses the implications of this archive in terms of art, virtual and academicals tradition. To have and to give access to the art knowledge, once art is understood as relation, is a problem of cultural mediation and it is experienced both by the educator and by the person educated in art.